SAT0446 Serum concentrations of 25-hydroxyvitamin d and metabolic syndrome and its components in nondiabetic systemic lupus erythematosus patients. (12th June 2018) - García-Carrasco, M.; Mendoza Pinto, C.; Cabrera-Jiménez, M.; Méndez-Martínez, S.; Etchegaray-Morales, I.; Zamora-Guinez, I.; Ruiz-Arguelles, A.; Cervera, R.
Abstract : Background: Increasing evidence has suggested a protective role of vitamin D in the metabolic syndrome (MetS). However, studies addressing this issue are limited in systemic lupus erythematosus (SLE). Objectives: We examined the relationship between serum 25-hydroxyvitamin D (25(OH)D) status and MetS in nondiabetic SLE patients. Methods: Cross-sectional analyses of the relationship between concentrations of 25(OH)D, MetS, and its components were made in 160 nondiabetic SLE women. MetS was defined according to the NCEP-ATP III criteria. Serum 25(OH)D was measured by chemiluminescent immunoassay. Serum 25(OH)D levels were categorised into quartiles (<16.6, 16.6–21.1, 21.2–26.3, ≥26.4 ng/ml). Results: A total of 79 (49.3%) of SLE women had MetS. Without adjusting for BMI or smoking, the odds of having MetS decreased according to increasing quartiles of vitamin D levels (P for trend=0.036). The odds ratio (OR) of having MetS was 0.39 (95% confidence interval: 0.16–0.97, p = 0.043) for the highest vs. the lowest quartile of vitamin D levels when adjusted by age. The crude OR of having elevated hypertriglyceridemia decreased according to increasing quartiles of vitamin D levels (P for trend=0.036). However, further adjustments for BMI and smoking removed the inverse association between vitamin D status and MetS and its individual components (Table). Conclusions: In nondiabetic SLE women with mild activity, the potential inverse relationship between vitamin D status and MetS may be attributable to the joint effects of individual obesity and smoking. Prospective studies are necessary to better determine the role of 25(OH)D in the incidence of MetS in SLE patients. Reference: [1] Wang X, Yan S, Liu C, Xu Y, Wan L, Wang Y, et al. Fracture risk and bone mineral density levels in patients with systemic lupus erythematosus: a systematic review and meta-analysis. Osteoporos Int2016:1413–1423. Acknowledgements: We thank David Buss for his valuable advice during this project. Disclosure of Interest: None declared